Evaluation of Fermented Rations Containing Physalis angulata (Ciplukan) on the Performance of Male Laying Chickens - Maulana, Fahmi Setia; Allaily, Allaily; zulfan, Zulfan; Daud, Muhammad (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
The cultivation of male laying chickens still has problems, namely the resulting performance is not maximized. Therefore research using fermented ciplukan plant (Physalis angulata) as a feed additive containing antioxidant compounds that function to improve performance needs to be carried out. This study aims to determine the effect of using fermented ciplukan flour on the performance of male laying chicken. This research was conducted at the Animal Husbandry Field Laboratory of the Faculty of Agriculture, Universitas Syiah Kuala, Indonesia. The material for this research was 100 DOC (Day Old Chicks) male laying chicken MB 502 from PT Japfa Comfeed Indonesia. This research method used a completely randomized design (CRD) with 4 treatments. The treatments were: control/without giving ciplukan (T0), giving 0.5% fermented ciplukan (T1), giving 0.75% fermented ciplukan (T2) and giving 1% fermented ciplukan (T3). Each treatment was repeated 5 times, each repetition consisting of 5 chickens. The parameters measured included ration consumption, body weight gain, final body weight, ration conversion and ration efficiency. Data were analyzed using Analysis of Variance, followed by Duncan's Multiple Range test. The results showed that the addition of fermented ciplukan flour in the ration had no significant effect on the consumption of male laying chicken. In conclusion, real treatment resulted in lower performance compared to commercial rations. However, T1, which is 0.5% ciplukan, tends to produce better performance.